Tomorrow's Living Room - Whitmarsh, Jason (Utah State University, University Libraries, 2009)
May Swenson Poetry Award Volume 13, with foreward by Billy Collins. Tomorrow's Living Room offers a pleasantly disorienting verbal territory. The collection is alternately wry and dark, hopeful and bleak, full of unexpected light and laugh-out-loud incongruities. We begin to see that the shape and the furniture of Jason Whitmarsh's world reflect our own world (and may in fact be universal), but we're considering them through completely new terms of engagement.